Hubungan Fungsi Kognitif dengan Kemandirian Lansia di Panti Sosial Tresna Werdha Budi Pertiwi dan Fakku Raqabah Muhammadiyah Kota Bandung - Erlina Fazriana; Dea Dini Fithriani; Kuslan Sunandar (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
In general, the physical condition of a person who has entered old age has decreased manifold. Every 3 seconds 1 person in the world has dementia. The incidence of dementia is increasing rapidly and it is currently estimated that 46.8 or 50 million people are diagnosed with dementia in the world. Dementia elderly are likely to have a high level of dependency. The research objective was to determine the relationship between cognitive function and the independence of the elderly at Tresna Werdha Budi Pertiwi and Fakku Raqabah Muhammadiyah Social Institutions, Bandung City. Correlational analytic research method with a cross sectional approach. Samples were taken using total sampling with 52 respondents as respondents. Data collection used the MMSE (Mini Mental State Examination) questionnaire to determine cognitive function and the Activity of Daily Living (ADL) questionnaire with the Modified Barthel Index instrument to determine independence. The data analysis method used is the Spearman rank test. The results of the analysis showed that 34 respondents (65.4%) had good cognitive function and 31 respondents (59.6%) had high independence. Spearman rank test results obtained p-value (0.001), then H1 is accepted. This means that there is a relationship between cognitive function and the independence of the elderly at the Tresna Werdha Budi Pertiwi and Fakku Raqabah Muhammadiyah Social Institutions, Bandung City. From this research, it is hoped that the management of the orphanage can provide media activities that can maintain the cognitive function of the elderly